Toward a European Coastal Observing Network to Provide Better Answers to Science and to Societal Challenges; The JERICO Research Infrastructure - Farcy, Patrick; Durand, Dominique; Charria, Guillaume; Painting, Suzanne J.; Tamminen, Timo; Collingridge, Kate; Grémare, Antoine J.; Delauney, Laurent; Puillat, Ingrid (Frontiers in Marine Science, 2019)
The coastal area is the most productive and dynamic environment of the world ocean, offering significant resources and services for mankind. As exemplified by the UN Sustainable Development Goals, it has a tremendous potential for innovation and growth in blue economy sectors. A major challenge for the scientific community making observations of the coastal marine environment is to integrate observations of Essential Ocean Variables for physical, biogeochemical and biological processes on appropriate spatial and temporal scales, and in a sustained and scientifically based manner. Coastal observations are important for improving our understanding of the complex biotic and abiotic processes in many fields of research such as ecosystem science, habitat protection, and climate change impacts. They are also important for improving our understanding of the impacts of human activities such as fishing and aquaculture, and underpin risk monitoring and assessment. The observations enable us to better understand ecosystems and the societal consequences of overfishing, disease (particularly shellfish), loss of biodiversity, coastline withdrawal and ocean acidification, amongst others. The European coastal observing infrastructure JERICO-RI, has gathered and organized key communities embracing new technologies and providing a future strategy, with recommendations on the way forward and on governance. The JERICO community acknowledges that the main providers of coastal observations are: 1) research infrastructures, 2) national monitoring programs and 3) monitoring activities performed by marine industries. The scope of this paper is to present some key elements of coastal science strategy to build it on long term. It describes how the pan-European JERICO community is building an integrated and innovation-driven coastal research infrastructure for Europe. The RI embraces emerging technologies which will revolutionize the way the ocean is observed. Developments in biotechnology (molecular and optical sensors, omics-based biology) will soon provide direct and online access to chemical and biological variables including in-situ quantification of harmful algae and contaminants. Using artificial intelligence (AI), Internet of Things will soon provide operational platforms and autonomous and remotely operated smart sensors. Embracing key technologies, high quality open access data, modelling and satellite observations, it will support sustainable blue growth, warning and forecasting coastal services and healthy marine ecosystem.